Climate change response measures in South African road transport sector: lessons from BRICS countries - Mashamaite, Maijane M. (Frontiers in Sustainable Cities, 2025)
Climate change can be mainstreamed into road transport sector and its policies by integrating mitigation actions, focusing on Green-House Gas (GHG) emission reduction, and building adaptive capacity for a climate-resilient road transport sector. Although research frequently emphasizes the difficulties of adaptation, this article explores the influence of climate change on the road transport network and examines how road transport contributes to climate change. Factors such as experiencing the costs of climate change, valuing the local ecosystem, resources availability, and political will is key to successful adaptation efforts. This article used desk research to gather information on mitigation and adaptation actions adopted by BRICS countries from various sources like government documents, the internet, books, articles and scientific reviews. It is therefore, deduced that BRICS countries can promote climate-friendly transport by prioritizing green logistics, green innovation and renewable natural resources, while promoting sustainable development and supporting renewable energy. BRICS represents Brazil, Russia, India, China, and South Africa, a group of developing economies working together to strengthen their economic and political influence. This article draws lessons from BRICS countries and conclude that South Africa should decrease fossil fuel use in the road transport sector for climate-friendly options.